Perception of civil servant’s on APIP capability as moderating vari-able on the relationship between the implementation of SPIP and SAKIP (Study on Salatiga City Government) - Limpat Akbar Yudanto; David Adechandra Ashedica Pesudo (The Indonesian Accounting Review, 2020)
This study discusses the government’s accountability performance. This study tried to obtain the evidence on the effect of SPIP (internal control system) Implementation on the SAKIP (accountability performance) implementation and APIP (internal auditor) Capability can strengthen the relationship between SPIP Implementation and SAKIP Implementation. This study helps to improve comprehension of the importance of the implementation of SPIP and the implementation of SAKIP to improve accountability performance as government and the importance of APIP capability can affect the relationship between the implementation of SPIP and SAKIP. It used the sampe consisting of 322 civil servants of Salatiga City Government. The variables used in this study include the dependent variable-SAKIP Implementation, the independent variable-SPIP Implementation, and the moderating variable-APIP Capability. This study uses primary data obtained from civil servants of Salatiga City Government. This data is a cross-section in the form of questionnaires using Moderated Regression Analysis with SPSS. The results show that SPIP Implementation affects SAKIP Implementation and APIP Capability strengthen the relationship between SPIP Implementation and SAKIP Implementation.